Health professionals', expert patients' and dieters' beliefs and attitudes about obesity. Issue 6 (18th March 2013) - McConnon, A.; Gribble, R.; Raats, M. M.; Stubbs, J.; Shepherd, R
Abstract Background Research has suggested that patients and treatment providers hold different beliefs and models of obesity. This could impact upon the consistency and quality of interventions for weight management. The present study investigated the attitudes and beliefs of health professionals, commercial weight management advisors (expert patients) and overweight and obese dieters, towards obesity. Methods Data were collected using a self‐administered questionnaire from 287 health professionals, 85 expert patients and 116 dieters. Respondents gave their views on obesity causation and consequences, and the most efficacious means to manage obesity. Demographic data and self‐reported height and weight were also collected. Factor analysis, analysis of variance and t‐tests were used to analyse the data. Results Health professionals, expert patients and dieters held similar models of obesity, identifying the same causes (lifestyle causes), consequences (medical consequences) and treatments (current recommended options) of obesity/overweight. Conclusions The findings of the present study indicate a broader similarity between beliefs and attitudes of those involved in obesity treatment and those that they aim to treat than was previously assumed. The concordance of beliefs between patients and treatment providers is an encouraging finding and may have important implications for public health strategies in this area.